149 Perceived sleep need, cumulative sleep deficit, and associations with daily affect in adolescents: 28 days over school & vacation. (3rd May 2021) - Shen, Lin; Wiley, Joshua; Bei, Bei
Abstract: Introduction: This study aimed to describe trajectories of daily perceived sleep need and sleep deficit across 28 consecutive days, and examine if cumulative sleep deficit predicts next-day affect. Methods: Daily sleep and affect were measured over 2 weeks of school and 2 weeks of vacation in 205 adolescents (54.1% females, Mage = 16.9 years). Each day, participants completed actigraphy and self-reported the amount of sleep needed to function well the next day (i.e., perceived sleep need), sleep duration, and high- and low-arousal positive and negative affect. Cumulative actigraphy and diary sleep deficit were calculated as difference between perceived sleep need and sleep duration, weighted by sleep deficit over the past 3 days. Cross-lagged, multilevel models were used to test cumulative sleep deficit as a predictor of next-day affect. Lagged affect, day of the week, study day, and sociodemographics were controlled. Results: Perceived sleep need was lower early in the school week, before increasing in the second half of the week. Adolescents accumulated sleep deficit across school days and reduced it during weekends. During weekends and vacations, adolescents' self-reported, but not actigraphy sleep duration, met perceived sleep need. Higher cumulative actigraphy sleep deficit predicted higher next-day high arousal negative affect; higher cumulative diary sleep deficit predicted higher negative affect (regardless of arousal), and lower low arousal positive affect the following day. Conclusion: Adolescents experienced sustained cumulative sleep deficit across school days, and whilst non-school nights appeared to be opportunities for reducing sleep deficit. Trajectories of sleep deficit during vacation suggested recovery from school-related sleep restriction. Cumulative sleep deficit was related to affect on a daily basis, highlighting the value of this measure for future research and interventions. Support (if any):